Enhancing Language Awareness through Folk Tale-Based Instruction: An Experimental Study in Language Education - Gladys Y. Sompotan, Amelia; Sambe, Nozomi; Bintang Pratiwi Harahap, Putri; Pinkan Warouw, Maya; Nitje Piri, Elvie (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: Language awareness is a key component of foreign language learning; however, it is often developed through grammar instruction presented without meaningful context, which limits learners’ ability to use language effectivelyUsing a quasi-experimental pretest–post-test control group design, 45 undergraduate students from two Indonesian universities were assigned to an experimental group receiving folk tale-based instruction and a control group receiving conventional grammar instruction over twelve 90-minute sessions. Quantitative data were collected using a standardized Language Awareness Instrument (LAI), written production tasks, and self-reflection measures, and analyzed using ANCOVA and related inferential statistics. Qualitative data from interviews and classroom observations were examined through thematic analysis.The results indicate that the experimental group achieved significantly greater gains in language awareness compared to the control group (F(1,85) = 112.34, p < .001, η² = .57). Learners exposed to folktale-based instruction demonstrated improved language use, reduced errors in writing, and enhanced awareness of language learning processes. These findings suggest that culturally grounded narrative-based instruction provides an effective and pedagogically meaningful approach to language teaching in EFL contexts.